Sowing innovation, harvesting prosperity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2018)
CTA focuses on youth entrepreneurship, digitalisation and climate-smart agriculture as key intervention areas for scaling development solutions. The empowerment of women is vital in our work. The revolution in information and communication technologies (ICT) over the last two decades has provided previously unimagined opportunities to boost agricultural productivity and build farmers’ resilience to climate shocks. As the impacts of climate change build across ACP countries, the necessity for farmers to adopt climate-smart agricultural techniques to not only ensure food security, but also improve their livelihoods, cannot be overstated.